2023
DOI: 10.1111/liv.15637
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of treatment with sofosbuvir/velpatasvir in patients aged 6–18 years with chronic hepatitis C—Results of the PANDAA‐PED study

Abstract: Background and AimsThe aim of this non‐commercial, open‐label, real‐life, non‐randomized clinical trial was to analyse the efficacy and safety of a pangenotypic regimen sofosbuvir/velpatasvir (SOF/VEL) in patients aged 6–18 years with chronic hepatitis C virus (HCV) infection.MethodsFifty patients qualified for the 12‐week treatment were divided into two weight groups: 15 children weighting between 17 and <30 kg received a fixed dose of 200/50 mg of SOF/VEL (tablet) once daily, and 35 patients weighting ≥30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…Similar data were found in the study by Pokorska-Spiewak et al for children 6–11 years of age. 25 These findings support the consideration of the use of sofosbuvir and velpatasvir combination therapy as a viable treatment option for young children with chronic hepatitis C.…”
Section: Special Populationssupporting
confidence: 63%
See 2 more Smart Citations
“…Similar data were found in the study by Pokorska-Spiewak et al for children 6–11 years of age. 25 These findings support the consideration of the use of sofosbuvir and velpatasvir combination therapy as a viable treatment option for young children with chronic hepatitis C.…”
Section: Special Populationssupporting
confidence: 63%
“… 28 A single center open-label study of 50 children and adolescents 6–18 years of age with HCV treated with SOF/VEL demonstrated 100% SVR at 12 weeks. 25 In this study, adverse events possibly or probably related to SOF/VEL were mild to moderate (headache, abdominal pain and asthenia were the most common) and were more common in the adolescents and none led to discontinuation of treatment. These observed virologic responses are comparable to the 95–99% SVR rates in the adult trials 22 , 29 and demonstrate the potency and effectiveness of this combination in eradicating the virus and preventing disease progression.…”
Section: Sofosbuvir and Velpatasvir Combination Therapymentioning
confidence: 55%
See 1 more Smart Citation
“…The results of the registration study have been confirmed in a recent real-world study using the same drug doses and treatment durations in adolescents. 16…”
Section: Children 3−5 Years Of Agementioning
confidence: 99%